Legal Protection of The Right to Health for People with Long-term Health Impact due to Disaster in Indonesia - Purba, Iman Pasu Marganda Hadiarto; Silitonga, Hanna Tabita Hasianna; Tauran, Tauran; Widianti, Alifia (Universitas Negeri Semarang, 2023)
Many disaster events occur in Indonesia which have an impact, especially on the health of the Indonesian people. Health impacts can occur directly and indirectly and some experience long-term impacts that affect their lives. The state cannot be absent in regulating various problems arising from disasters in Indonesia. Therefore, the legal regulation of the right to health for long-term health impact sufferers due to disaster Indonesia must be examined. The study used normative legal research, a study approach to legislation, and library research. State policy ensures that the right to health is realized through legal products (primary legal materials) reviewed and then described and analyzed in answering how to fulfill the right to health in Indonesia due to disaster. As a result, the Indonesian Government has already ensured the fulfillment of the right to health of every citizen. However, Government should issue advanced services regulations as soon as possible to regulate the handling of long-term health impact sufferers due to disaster in Indonesia.